2020
DOI: 10.1101/2020.07.21.214874
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Transcriptional Switch Governing Fibroblast Plasticity Underlies Reversibility of Chronic Heart Disease

Abstract: In diseased organs, stress-activated signaling cascades alter chromatin, triggering broad shifts in transcription and cell state that exacerbate pathology. Fibroblast activation is a common stress response that worsens lung, liver, kidney and heart disease, yet its mechanistic basis remains poorly understood1,2. Pharmacologic inhibition of the BET family of transcriptional coactivators alleviates cardiac dysfunction and associated fibrosis, providing a tool to mechanistically interrogate maladaptive fibroblast… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…3b ). Consistently, recently identified markers of fibroblast activation 25 also increased, including MEOX1, SERPINE1 (also known as plasminogen activator inhibitor-1 which induces clotting), TNC, VEGFC , and IL4R , ( Fig. 3c,d ).…”
Section: Mainsupporting
confidence: 85%
“…3b ). Consistently, recently identified markers of fibroblast activation 25 also increased, including MEOX1, SERPINE1 (also known as plasminogen activator inhibitor-1 which induces clotting), TNC, VEGFC , and IL4R , ( Fig. 3c,d ).…”
Section: Mainsupporting
confidence: 85%
“…Here, we applied CellWalker to neurodevelopment. In another study, we used CellWalker to map transcriptional disease states from mouse heart data to scATAC-seq data in matched tissues and uncovered cell type-specific enhancers activated by stress [31] Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent study demonstrated that MEOX1 regulated the pro-fibrotic function and was implicated in the fibrosis of multiple human organs including the heart, liver, lung and kidney. 41 AEBP1 (also named ACLP ) has been implicated in the fibroblast activation of lung fibrosis. 42 However, our study also identified an array of novel genes and pathways that have not been explicitly implicated in fibrosis.…”
Section: Discussionmentioning
confidence: 99%